Bank Restructuring in Sub-Saharan Africa : Lessons Learned - Deschamps, Jean-Jacques; Bonnardeaux, James (World Bank, Washington, DC, 2012)
A review of bank restructuring operations in seven countries of Sub-Saharan Africa - Benin, Cote d'Ivoire, Ghana, Kenya, Tanzania, Uganda, and Mozambique indicates that not all these efforts have succeeded. Interventions to break-up or privatize dominant state-owned banks are, in some cases, still going on, years after initial actions were agreed upon with local authorities. Hence, the importance of drawing lessons from these experiences for other African countries undertaking similar efforts. The review represents the first systematic attempt by the World Bank to analyze and compare the outcomes of bank restructuring programs in individual countries in the region.